2018
DOI: 10.1002/app.46561
|View full text |Cite
|
Sign up to set email alerts
|

Study of denaturation and composition‐dependent poly(ethylene oxide)–soy protein interactions: Structures and dielectric polarization

Abstract: The significance of aggregated protein structures in tuning structures and dielectric polarization of poly(ethylene oxide) (PEO)/soy protein isolate (SPI) films was studied. The aggregated protein structures, subjected to denaturation processes, are expected to alter polymer–protein interactions, leading to diverse material structures, and properties. However, this is still insufficiently understood. In this study, SPI was modified via different denaturation processes including heat, sonication, and pH‐control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…By blending with proteins, the bio-performances of petroleum-based polymers, such as biocompatibility, degradation rate and solubility were improved [18,19]. In our preliminary studies, we found that the diverse polymer-protein interactions played important roles in tuning microstructures and properties of the resulting composites [20][21][22][23][24]. 2S fraction of protein was studied as a non-covalent surfactant for polymer nanocomposites [20].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…By blending with proteins, the bio-performances of petroleum-based polymers, such as biocompatibility, degradation rate and solubility were improved [18,19]. In our preliminary studies, we found that the diverse polymer-protein interactions played important roles in tuning microstructures and properties of the resulting composites [20][21][22][23][24]. 2S fraction of protein was studied as a non-covalent surfactant for polymer nanocomposites [20].…”
Section: Introductionmentioning
confidence: 91%
“…With the variation of protein modifier concentration, the properties of the poly(vinylidene fluoride) (PVDF), including dielectric constant and ferroelectric hysteresis, were remarkably altered [21]. Moreover, we found that by controlling the denaturation conditions of protein, protein modifiers possessed different structures and properties, and were able to vary the microstructures and dielectric properties of hydrophilic poly(ethylene oxide) (PEO) [23] and hydrophobic PVDF polymers [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation